The demand for African technicians : a case study - Bloch, Nigel (Michaelis School of Fine Art, 2023)
Technological advance and industrialization lead to changes in the structure of the demand for labour. A relative decline in the demand for agricultural and 1mskilled workers occurs together with a relative increase in demand for workers in the skilled categories (professional, technical, managerial, and administrative; clerical and sales; service; and skilled industrial workers, e.g., artisans) which increases as a percentage of total employment over time. This pattern has been followed with great consistency in industrializing countries (Schreiner, 1967; 1961 Education Panel, 1963, 1966) and has certainly been the case in the United States (United States Department of Labour, 1963, 1964, 1965). Francis Wilson has written that 11 the signature tune of South Africa's economic history is surely the wailing of employers over the shortage of labour 11 (Wilson, 1972, p.86). In this study I will examine an aspect of this statement by looking at the concept (Section I), and reality in so far as it can be quantified (Section II), of the 'skills shortage' in South Africa. The latter is explored further in Section III in which the demand for African technicians discovered in fieldwork by the writer is discussed. Section IV is an examination of the extent to which current educational policy provides a supply of Africans educated at the higher levels to meet this demand. Section V contains the conclusion and recommendations of the study.